Study of the impact of bentonite on the physico-mechanical and flow properties of cement grout. Issue 1 (1st January 2018) - Mesboua, Noureddine; Benyounes, Khaled; Benmounah, Abdelbaki
Abstract: Cement-based grouts have been used successfully to repair cracks in many concrete structures, to ensure the stability of slopes or retaining walls and to reinforce soils or rock foundations. This study aims to the use of Algerian bentonite in cement grout as a partial replacement for cement. We have optimized the fresh state of cement grouts made from binary binders, by studying their physical and rheological properties. So as to analyze the effect of bentonite on the behavior of the grout, various tests such as X-ray diffraction (XRD), laser granulometry, and X-ray fluorescence spectrometry(XRF) of cement and bentonite have been investigated. This paper examines the effect of bentonite on the fresh and hardened of cement based grouts so as to develop a flow and stable grout. The experimental procedure consists to study the behaviour of mixtures substituted by different bentonite contents (8, 10, 12, 14, 16 and 18%) subjected to physical (density and bleeding), and Rheological (mini-slump cone) tests. Mechanical strength test of the hardened grouts was analysed at 28 days. Results show the compressive strength decreased slightly with increasing bentonite dosage.The assess of pozzolanic activity was determined from the strength activity index (SAI). All the mixtures have shown that the strength activity indices were higher than 75%, which were conform to the ASTM C618 standard